2022
DOI: 10.3390/land11091414
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Mercury Concentrations and Greenhouse Gas Emissions of Pristine and Managed Hemiboreal Peatlands

Abstract: We assessed total mercury (THg) concentrations and greenhouse gas (GHG) emissions in pristine and managed hemiboreal peatlands in Latvia, aiming to identify environmental factors that potentially affect their variation. The THg concentrations in soil ranged from <1 µg kg−1 to 194.4 µg kg−1. No significant differences between THg concentrations in disturbed and undisturbed peatlands were found, however, the upper soil layer in the disturbed sites had significantly higher THg concentration. During May–August,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 93 publications
2
4
1
Order By: Relevance
“…In this study, the highest total soil CO 2 efflux released from perennial grassland in summer (average of 1.16 g CO 2 m −2 h −1 ) is well in line with a recent study evaluating total soil CO 2 efflux in Histosols under grasslands in Sweden and Latvia [ 40 , 41 ]. Also, similar results of total soil CO 2 efflux from forest sites were obtained in the study conducted in Latvia [ 41 ]. Studies investigating annual CO 2 emissions have reported that total soil CO 2 efflux in winter ranged up to 5–30% of the total CO 2 efflux measured during the growing season [ 39 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the highest total soil CO 2 efflux released from perennial grassland in summer (average of 1.16 g CO 2 m −2 h −1 ) is well in line with a recent study evaluating total soil CO 2 efflux in Histosols under grasslands in Sweden and Latvia [ 40 , 41 ]. Also, similar results of total soil CO 2 efflux from forest sites were obtained in the study conducted in Latvia [ 41 ]. Studies investigating annual CO 2 emissions have reported that total soil CO 2 efflux in winter ranged up to 5–30% of the total CO 2 efflux measured during the growing season [ 39 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…There is no clear answer to the question of the role of SOM in metal retention in soils (Bārdule et al, 2022; Christl et al, 2005; Donisa et al, 2003; Mi et al, 2018; Quenea et al, 2009; X. S. Wang, 2008). Metal depletion of soils with high organic matter content may result from the solubilising effect of SOM, whereas metal accumulation may be due to the strong association of metal and organic matter in solid phase (Staunton, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, regardless of molecular weight, inactive or blocked chelators do not alter the soil's ability to retain elements, even in the presence of significant amounts of SOM (Christl et al, 2001; He et al, 2020; Pandey et al, 2000). The observed discrepancies may also be due to the fact that the above‐mentioned studies refer to soil samples taken from various depths, which may contain different soil horizons characterised by different OM contents, rather than individual soil horizons (Bārdule et al, 2022; Christl et al, 2005; Donisa et al, 2003; Mi et al, 2018; Quenea et al, 2009; X. S. Wang, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, after peat extraction, any rehabilitation measures including plant establishment will likely result in net carbon removals because in the first years the biomass stock will build up. Bārdule et al ( 2022 ) suggested that wet peatlands do not achieve lower emissions than drained peatlands. However, they measured only once per month over a period of only four months, during only one vegetation period.…”
Section: Climate Impact Of Peatland Forestrymentioning
confidence: 99%